María Rojas Tejada. La mujer moderna y la educación de la mujer en el siglo XX (2014)
María Rojas Tejada was an important part of a fundamental and leading educational process for Colombia early in the 20th century, helping with the introduction of foreign ideas coming from a current called new school; these ideas were contrary to the traditional ones of the country. Her role was never apart from her fight for the woman’s right to be education, bearing in mind that Modernity and introduction of women in the labor world represented new challenges and opened new educational perspectives for them.Despite the woman’s place in society was based on a deterministic view that is still seen in our society, María Rojas not only had the idea of a modern woman but raised her voice on behalf of women, breaking paradigms and promoting new ideas around women